New ACR/EULAR 2022 classification criteria for ANCA-associated vasculitis - T. V. Beketova (Научно-практическая ревматология, 2023)
The new 2022 classification criteria for antineutrophil cytoplasmic antibodies associated vasculitis (AAV), proposed by the American College of Rheumatology (ACR) and the European Alliance of Associations for Rheumatology (EULAR), was an important stage in the development of the doctrine of systemic vasculitis. Based on the analysis of large international cohorts, the criteria for granulomatosis with polyangiitis and eosinophilic granulomatosis with polyangiitis were revised, and classification criteria for microscopic polyangiitis were proposed for the first time. The creation’s history of the AAV classification criteria is discussed over the past three decades, and their limitations are considered. It should be noted, the ACR/EULAR 2022 criteria were developed for creating homogeneous groups of patients for scientific studies and cannot be widely used in clinical practice for the various AAV nosological forms diagnosis, primarily at early stage of the disease or mono organ damage (for example, kidneys). As before, decisive importance in AVV diagnostic belong to a detailed clinical analysis and a complete examination of patients to identify pathognomonic symptoms, including asymptomatic ones.